2005
DOI: 10.1108/09540910510613501
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surface finish on the reliability of lead free and tin lead chip scale package solder joints

Abstract: PurposeThe effects of thermal fatigue and printed circuit board (PCB) surface finish on the pull strength, failure modes and reliability of chip scale package (CSP) solder joints were investigated.Design/methodology/approachMechanical pull test, metallographic examination and electrical measurement were used. Tin lead (Sn‐Pb) and lead free (Sn‐Ag‐Cu) alloys were used with Au/Ni and organic solderability preservative (OSP) surface finishes.FindingsThe experimental results showed that the pull strength of the Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The changes in surface finish add extra concerns in terms of reliability, as most failures of devices occur at the relatively weak intermetallics between the bulk solder and the pads of the components and the PCBs. Recently Huang et al (2005) have conducted a study of the effect of organic solderability preservative (OSP) and electroless nickel immersion gold (ENIG) finishes on the thermal fatigue of chip scale package (CSP) solder joints produced from SAC 305 and SnPb. The results showed that the OSP finish performed better with the SnPb, however there was little difference between the finishes for SAC 305 with ENIG slightly better.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in surface finish add extra concerns in terms of reliability, as most failures of devices occur at the relatively weak intermetallics between the bulk solder and the pads of the components and the PCBs. Recently Huang et al (2005) have conducted a study of the effect of organic solderability preservative (OSP) and electroless nickel immersion gold (ENIG) finishes on the thermal fatigue of chip scale package (CSP) solder joints produced from SAC 305 and SnPb. The results showed that the OSP finish performed better with the SnPb, however there was little difference between the finishes for SAC 305 with ENIG slightly better.…”
Section: Introductionmentioning
confidence: 99%
“…With this continuous miniaturization and increasing functionality of electronic components, the microelectronic industry keep moving towards fine pitch devices. Area array components have evolved to meet the demands of the industry and the chip scale package (CSP) is therefore becoming one of the main products in the integrated circuit (IC) industry [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this technology, the proper selection of the surface finishes for the soldering pads on the component and PCB sides, along with that of the solder alloys which are typically Sn-based, is one of the major concerns related to solder joint reliability. [1][2][3][4][5] The most common surface finish on the component side is electrolytic Ni/Au plated over the Cu pad of the flexible substrate. During the reflow process, the Au layer is quickly dissolved into the molten solder and then the Ni layer is exposed to and reacts with the solder.…”
Section: Introductionmentioning
confidence: 99%